The Idea Is Mine! An Empirical Examination on the Effect of Leaders’ Credit Claiming on Employees’ Work Outcomes - Chen, Siyuan; Li, Daiheng; Yang, Chun; Zhang, Xijing; Hou, Liang (Frontiers in Psychology, 2022)
Existing studies mainly explored the detrimental effect of employee credit claiming, and little is known about how leader credit claiming can affect employees. Based on affective events theory and relative deprivation theory, we explore how leader credit claiming affects employee work outcomes (i.e., voice behavior and job performance) by the research methods of literature review, interview, and empirical questionnaire. With a sample of 418 matched leader–employee pairs from a large manufacturing company, we find that leader credit claiming influences employee work outcomes through the mediating role of employee anger and perceived unfairness. Additionally, we determine that leader credit-claiming attribution (i.e., to protect employees) has a moderating influence on the relationship between credit claiming and anger and between credit claiming and perceived unfairness. The results support all hypotheses. Furthermore, we discuss the theoretical and practical implications of the findings.